2020
DOI: 10.15388/namc.2020.25.16520
|View full text |Cite
|
Sign up to set email alerts
|

Lagrange problem for fractional ordinary elliptic system via Dubovitskii–Milyutin method

Abstract: In the paper, we investigate a weak maximum principle for Lagrange problem described by a fractional ordinary elliptic system with Dirichlet boundary conditions. The Dubovitskii-Milyutin approach is used to find the necessary conditions. The fractional Laplacian is understood in the sense of Stone-von Neumann operator calculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Two illustrative examples were presented. In particular, we observed that [22,Thm. 4] cannot be used to problem (16)- (17).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Two illustrative examples were presented. In particular, we observed that [22,Thm. 4] cannot be used to problem (16)- (17).…”
Section: Discussionmentioning
confidence: 74%
“…Similarly (using assumption (A) and analogous arguments as in [22,Prop. 3.2]), we obtain a differentiability property of the mapping F 0 k 1 , whereby the differential…”
Section: Necessary Optimality Conditionsmentioning
confidence: 85%
See 3 more Smart Citations